Modelagem hidrossedimentológica da bacia hidrográfica do rio Betume, Baixo São Francisco sergipano - Salazar, Ricardo David Castillo (2016)
The rational use of water resources of a river basin is essential for sustainability and socio-economic development. Proper land use and vegetation cover is directly related to the conservation of water resources and the preservation of the environment. An important tool for the representation and understanding of the hydrological behavior of a watershed is modeling. In this sense, from the quantitative monitoring of the flow, used the SWAT (Soil and Water Assessment Tool) model, which is used to study the dynamics of the hydrossedimentological river basin Betume in the Lower São Francisco in the estate of Sergipe. The model uses a specialized database of the basin, consisting of geographical, soil, hydrological and climate information. Had accomplished three scenarios depending on the land use simulating the production of water and sediments. The modeling demonstrated that the dynamics of the basin is mainly based on the base flow stream. Of the three hypothetical scenarios performed, the Reforestation scenario produced the lowest water and sediment production rate, and the Agriculture scenario had the highest rates. Having noticed the changes in land use and occupation influence the water production system and sediments in the basin. Overall, it is noteworthy that the presence of native vegetation ensures the highest water availability for multiple uses of water in the region.